Exploring the Concept of 'Spirituality' in Coelho's Brida: The Search for Inner Awareness and Personal Integration - Seng, Foong Soon (SARE: Southeast Asian Review of English, 2017)
The subjection of women based on patriarchal traditions alongside a dualistic system has been responsible for the denial of equal status to women. For example, associating women with nature is one of the strategies used to 'imprison' and 'lock' women in this vulnerable position. Under this system, women are 'chained' to the domestic sphere. When this 'tradition' is passed on from one generation to another, society seems to perceive this as the universal truth. By establishing the sense of dualism between 'male' and 'female', a parallel between the culture/nature polarities is drawn, where men are associated with culture and women with nature. The association or the clear demarcation between men and women is supported by the concept of the 'logic of domination' (Warren, 2000: 47). This logical structure of argumentation justifies the domination and subordination of women as the weaker beings. Such claims tend to place women as the locus of passivity, namely as weak, submissive, and emotional.